EFISIENSI FAKTOR FAKTOR PRODUKSI USAHA BUDIDAYA IKAN LELE DUMBO (Clarias garipenus): STUDI KASUS PADA ALUMNI PESERTA PELATIHAN BUDIDAYA IKAN DI BPPP BANYUWANGI) - Sumartin Sumartin (Faculty of Science and Technology University Ibrahimy, 2017)
This study aims to analyze the level of economic, technical and price efficiency of the catfish cultivation of the participants of catfish cultivation training at BPPP Banyuwangi, while analyzed includes factors that affect the efficiency of production. The data analysis used is Cobb Douglas stochastic frontier analysis estimated by Ordinary Least Square Method (OLS). OLS method aims to determine the efficiency of the average performance of catfish cultivation business. Estimation with maximum likelihood (EML) method aims to know the level of technical efficiency, using frontier computation program version 4.1. To know the efficiency of the price is known by calculating the value of marginal product (VMP) of the production factor. The results showed that the level of economic efficiency (EML) catfish cultivation business in regency Tabanan Bali, Banyuwangi, Blitar, three factors of production are in the rational area, but not yet efficient because the value of coefficient of pond (X1) 0198, fish fry (X4) 0456 and feed (X5) 0423. While the other four factors of production are inefficient, because they are in irrational area with negative coefficient value, ie fertilizer production factor (X2) -1.74, lime (X3) -4.18, probiotic (X6) -1.54, labor (X7) -9.59 . and value of experience variables of cultivators (Z1) 0.3200385, age of fishery cultivators (Z2) 0.2602872 and formal education (Z3) -0.0571254. For the efficiency of price obtained value of VMP each factor of production Area of ​​pond (X1) 0,00004745, NPM Lime (X4) 0,00000026 and NPM Feed (X5) 0,00000012. For NPM of the four factors of production Fertilizer (X2) -0,00791951, Lime (X3) -0.01723183 Probiotics (X6) -0.01819837 and Labor (X7) -0.17465781. Overall price efficiency achieved is 0.21796 and economic efficiency of 3.48147